Digital transformation for MSMEs: Boosting sales through e-commerce and social media - Surahman, Surahman; Hariyadi, Sugeng; Barus, Bela; Batoteng, Hendrik; Rahmadhani, Adestya; Aisyayah, Wulan Nur; Pustpita, Aulia Oktaviani; Febrianti, Nadya (Universitas Muhammadiyah Magelang, 2025)
This community service activity aims to enhance the effectiveness of digital marketing for retail Micro, Small, and Medium Enterprises (MSMEs), specifically Pasundan Gorden, through the integration of e-commerce and social media. The activities encompassed the design of a user-friendly e-commerce website, the development of focused social media campaigns, and the evaluation of their impact on business performance. Implementation methods included identifying participant needs, preparing training materials, conducting interactive workshops, and post-training evaluation. Results demonstrated a significant improvement in participants' understanding and skills in digital marketing, with average scores increasing from 60 to 85. Furthermore, a responsive website and focused social media campaigns were created, leading to increased consumer engagement, brand awareness, and sales. Dissemination of information on content marketing, SEO, and augmented reality is recommended to enhance customer loyalty. Thus, this activity serves as a model for other MSMEs to improve digital competitiveness through planned strategy implementation and continuous evaluation.